Enhancing Visible Light Photocatalysis with Hydrogenated Titanium Dioxide for Anti-Fouling Applications. (10th July 2018) - Al Zaim, Safa; Raza, Aikifa; Lu, Jin You; Choi, Daniel; Fang, Nicholas X.; Zhang, TieJun
ABSTRACT: Anti-organic fouling performance of titanium dioxide (TiO2 ) can be enhanced by extending its light absorption and photocatalytic capability from ultra-violet to the visible range through hydrogenation. In this work, we aim at studying the impact of hydrogenation on the performance of both electron beam-deposited TiO2 thin films and hydrothermally grown TiO2 nanostructures on titanium substrates. Hydrogenation of these TiO2 -deposited titanium substrates (TiO2 /Ti) are achieved in relatively low-temperature low-pressure chemical vapor deposition chamber without any noble diatomic hydrogen dissociation catalyst, such as platinum. Our study shows that these hydrogenated TiO2 /Ti have better light absorption ability and the titanium substrate itself serves as the active catalyst for hydrogen dissociation and diffusion. By applying hydrogenation to the TiO2 nanostructures, we can enhance photocatalytic performance by 50% through methylene blue degradation experiments. We have also evaluated the effect of hydrogenation on carrier density and mobility in TiO2 /Ti. We recommend the hydrogenation of hydrothermally grown TiO2 nanostructure on titanium substrates for scalable photocatalytic applications.